Genomic characterization of the uncultured Bacteroidales family S24-7 inhabiting the guts of homeothermic animals. Issue 1 (December 2016) - Ormerod, Kate; Wood, David; Lachner, Nancy; Gellatly, Shaan; Daly, Joshua; Parsons, Jeremy; Dal'Molin, Cristiana; Palfreyman, Robin; Nielsen, Lars; Cooper, Matthew; Morrison, Mark; Hansbro, Philip; et al.
Abstract Background Our view of host-associated microbiota remains incomplete due to the presence of as yet uncultured constituents. TheBacteroidales familyS24-7 is a prominent example of one of these groups. Marker gene surveys indicate that members of this family are highly localized to the gastrointestinal tracts of homeothermic animals and are increasingly being recognized as a numerically predominant member of the gut microbiota; however, little is known about the nature of their interactions with the host. Results Here, we provide the first whole genome exploration of this family, for which we propose the name "Candidatus Homeothermaceae, " using 30 population genomes extracted from fecal samples of four different animal hosts: human, mouse, koala, and guinea pig. We infer the core metabolism of "Ca. Homeothermaceae" to be that of fermentative or nanaerobic bacteria, resembling that of relatedBacteroidales families. In addition, we describe three trophic guilds within the family, plant glycan (hemicellulose and pectin), host glycan, and α-glucan, each broadly defined by increased abundance of enzymes involved in the degradation of particular carbohydrates. Conclusions "Ca. Homeothermaceae" representatives constitute a substantial component of the murine gut microbiota, as well as being present within the human gut, and this study provides important first insights into the nature of their residency. The presence of trophic guilds within the family indicates the potential for niche partitioning and specific roles for each guild in gut health and dysbiosis.